Improving the efficiency of an optical-to-terahertz converter using sapphire fibers - N. V. Zenchenko; D. V. Lavrukhin; I. A. Glinskiy; D. S. Ponomarev (Российский технологический журнал)
Objectives. The study aims to improve the efficiency of a large-area photoconductive terahertz (THz) emitter based on an optical-to-terahertz converter (OTC) having a radiating area of 0.3 × 0.3 mm2 for generating high-power THz radiation by using an array of close-packed profiled sapphire fibers having a diameter in the range of 100–300 μm as focusing optics.Methods. As a photoconductive substrate, we used a semi-infinite LT-GaAs layer (low-temperature grown GaAs; GaAs layer grown by molecular beam epitaxy at a low growth temperature). Additional Si3N4 and Al2O3 layers are intended for reducing leakage currents in the OTC and reducing the reflection of the laser pump pulse from the air/semiconductor interface (Fresnel losses), respectively, at a gap width of 10 μm. For forming the antenna electrodes and feed strips, the Ti/Au metal system was used. The simulation was carried out by the finite element method in the COMSOL Multiphysics environment.Results. The use of a profiled sapphire fiber whose diameter has been optimized with respect to the gap parameters to significantly increase the concentration of charge carriers in the immediate vicinity of the electrodes of an OTC is demonstrated. The integrated efficiency of a large-area photoconductive THz emitter was determined taking into account the microstrip topology of the array with a characteristic size of feed strips proportional to the gap width in the OTC and with the upper (masking) metal layer. The maximum localization of the electromagnetic field in close proximity to the edges of electrodes at the “fiber–semiconductor” interface is achieved with a profiled sapphire fiber diameter of 220 μm.Conclusions. By optimizing the diameter of the sapphire fiber, the possibility of improving the localization of incident electromagnetic waves in close proximity to the edges of the OTC electrodes by ~40 times compared to the case without fiber, as well as increasing the overall efficiency of a large-area emitter by up to ~7–10 times, was demonstrated.